The Evolution of Green Politics: Development and Change within European Green Parties - Burchell, Jon (Earthscan, 2002)
The emergence of Green parties throughout Europe during the 1980s marked the arrival of a new form of political movement and a challenge to existing party models. This work presents an in-depth, thematic comparative approach to the analysis of recent Green party development and change, questioning whether the process of party evolution has resulted in the ideological dilution of Green ideals and objectives. With Green parties across Europe experiencing a significant upturn in support in recent years, if we are to gain a clearer picture of the impact Green parties should have in the 21st century we need to understand the issues and themes that have shaped their re-emergence as a more mature political challenge.